Molecular markers for tracking the origin and worldwide distribution of invasive strains of Puccinia striiformis. Issue 9 (20th March 2016) - Walter, Stephanie; Ali, Sajid; Kemen, Eric; Nazari, Kumarse; Bahri, Bochra A.; Enjalbert, Jérôme; Hansen, Jens G.; Brown, James K.M.; Sicheritz‐Pontén, Thomas; Jones, Jonathan; de Vallavieille‐Pope, Claude; Hovmøller, Mogens S.; et al.
Abstract: Investigating the origin and dispersal pathways is instrumental to mitigate threats and economic and environmental consequences of invasive crop pathogens. In the case of Puccinia striiformis causing yellow rust on wheat, a number of economically important invasions have been reported, e.g., the spreading of two aggressive and high temperature adapted strains to three continents since 2000. The combination of sequence‐characterized amplified region (SCAR) markers, which were developed from two specific AFLP fragments, differentiated the two invasive strains, Pst S1 and Pst S2 from all other P. striiformis strains investigated at a worldwide level. The application of the SCAR markers on 566 isolates showed that Pst S1 was present in East Africa in the early 1980s and then detected in the Americas in 2000 and in Australia in 2002. Pst S2 which evolved from PstS1 became widespread in the Middle East and Central Asia. In 2000, Pst S2 was detected in Europe, where it never became prevalent. Additional SSR genotyping and virulence phenotyping revealed 10 and six variants, respectively, within PstS1 and PstS2, demonstrating the evolutionary potential of the pathogen. Overall, the results suggested East Africa as the most plausible origin of the two invasive strains. The SCAR markers developed in the present study provide a rapid, inexpensive, and efficient tool to track the distribution of P. striiformis invasive strains, PstS1 and PstS2 . Abstract : The study reports on the development and application of two strain‐specific SCAR markers for tracking the distribution of invasive and high temperature adapted strains of the wheat yellow rust fungus, P. striiformis . We were also able to identify East Africa as the most likely origin of the aggressive strains. The worldwide spread and establishment of the two invasive strains is addressed in the context of epidemic outbreaks of yellow rust disease and deployment of host resistance.